2007
DOI: 10.1111/j.1462-2920.2007.01403.x
|View full text |Cite
|
Sign up to set email alerts
|

Viability, diversity and composition of the bacterial community in a high Arctic permafrost soil from Spitsbergen, Northern Norway

Abstract: The viable and non-viable fractions of the bacterial community in a 2347-year-old permafrost soil from Spitsbergen were subjected to a comprehensive investigation using culture-independent and culture-dependent methods. LIVE/DEAD BacLight staining revealed that 26% of the total number of bacterial cells were viable. Quantitatively, aerobic microcolonies, aerobic colony-forming units and culturable anaerobic bacteria comprised a minor fraction of the total number of viable bacteria, which underlines the necessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
123
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(135 citation statements)
references
References 81 publications
10
123
1
Order By: Relevance
“…It is more likely that the isolates cultivated here were of subglacial origin, as no representatives of the genus were found in surface ice or anywhere else along the transect. For example, recently described Leifsonia species were isolated from cold habitats such as soil near a Himalayan Glacier, Southern Ocean sediment (Pindi et al 2009), Antarctic pond cyanobacterial mat (Reddy et al 2003), and Spitsbergen permafrost (Hansen et al 2007), suggesting this genus is well adapted to life in polar and alpine ecosystems. One of its ecological functions could be supplying autotrophs with phosphorus and metal ions of biological importance such as Fe, Mn, Ca, K, and Mg by weathering of poorly available sources (insoluble mineral deposits).…”
Section: Microbial Community Along Transectmentioning
confidence: 99%
See 2 more Smart Citations
“…It is more likely that the isolates cultivated here were of subglacial origin, as no representatives of the genus were found in surface ice or anywhere else along the transect. For example, recently described Leifsonia species were isolated from cold habitats such as soil near a Himalayan Glacier, Southern Ocean sediment (Pindi et al 2009), Antarctic pond cyanobacterial mat (Reddy et al 2003), and Spitsbergen permafrost (Hansen et al 2007), suggesting this genus is well adapted to life in polar and alpine ecosystems. One of its ecological functions could be supplying autotrophs with phosphorus and metal ions of biological importance such as Fe, Mn, Ca, K, and Mg by weathering of poorly available sources (insoluble mineral deposits).…”
Section: Microbial Community Along Transectmentioning
confidence: 99%
“…In this respect, the bioleaching properties of Leifsonia spp. have been widely recognized (Hansen et al 2007;Delvasto et al 2008;Frey et al 2010).…”
Section: Microbial Community Along Transectmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies do not reveal which genes are actively expressed and thus which potential biochemical functions are being realized at a given time. In permafrost, this distinction between metabolic potential (as indicated by genomes) and metabolic activity may be especially important because constant subzero temperatures create excellent preservation conditions and inactive or dead cells (along with their genomes) may remain in the soil for extended periods of time (Dmitriev et al 2001, Hansen et al 2007. To better determine which parts of a community's overall functional potential are actually being realized by microbial metabolic activity, metagenomic data can be complemented with other approaches that provide information about gene expression.…”
Section: Total Community Activity: Other -Omics Strategiesmentioning
confidence: 99%
“…The potential for sulfur metabolism is clearly present in permafrost microbes. A sulfur-reducing bacterium was isolated from ancient permafrost (Vatsurina et al 2008), and 16S rRNA gene sequences from sulfate-reducing and sulfur-oxidizing bacteria were found in permafrost (Hansen et al 2007, Steven et al 2007). Taxonomic assignment of metagenomic sequences to sulfate reducers and the presence of genes involved in sulfate reduction also revealed that microbes that use sulfate as a TEA are present in permafrost (Chauhan et al 2014, Lipson et al 2013.…”
Section: Sulfur Cyclementioning
confidence: 99%